Razumikhin and Krasovskii stability of impulsive stochastic delay systems via uniformly stable function method - Pan, Lijun; Hu, Jianqiang; Cao, Jinde (Nonlinear Analysis: Modelling and Control, 2023)
This paper generalizes Razumikhin-type theorem and Krasovskii stability theorem of impulsive stochastic delay systems. By proposing uniformly stable function (USF) in the form of impulse as a new tool, some properties about USF and some novel pth moment decay theorems are derived. Based on these new theorems, the stability theorems of impulsive stochastic linear delay system are acquired via the Razumikhin method and the Krasovskii method. The obtained results enhance the elasticity of the impulsive gain by comparing the previous results. Finally, numerical examples are given to demonstrate the effectiveness of theoretical results.